Philosophical Writings - Beauvoir, Simone de, 1908-1986 (Book collections on Project MUSE., 2004)
"As the first complete, scholarly edition of Beauvoir's philosophical essays in English translation, this volume aims at nothing less than the transformation of Simone de Beauvoir's place in the canon. Despite growing interest in her philosophy, Beauvoir remains widely misunderstood and is typically portrayed as a mere philosophical follower of her companion, Jean-Paul Sartre. In Philosophical Writings, Beauvoir herself shows that nothing could be further from the truth."--Jacket.